KONTEN YOUTUBE SEBAGAI JAMINAN BAGI PELAKU EKONOMI KREATIF DALAM PERSPEKTIF HUKUM JAMINAN - Agus Suwandono (LPPM Universitas Ekasakti Padang, 2023)
Youtube content as a creative economy work has been recognized as Intellectual Property that can be used as collateral. This, of course, can optimize the potential of creative economy actors to increase their business. However, this also still raises debate about the legal certainty of Youtube content as a guarantee for creative economy business actors from the perspective of guarantee law. This research is normative juridical research with an emphasis on secondary data. The research specification is descriptive-analytical, using a qualitative normative analysis method using a deductive approach to conclude. The results showed that the facilitation mechanism for intellectual property-based financing schemes begins with copyright registration of YouTube content, verification and assessment of collateral by a bank or non-bank financial institutions, financing or credit agreements followed by guarantee charging contract, and recording in the financing facilitation system for creative economy business actors. The legal certainty of YouTube content as a guarantee for creative economy actors from a legal perspective, guarantees do not protect creditors. This is because the value of intellectual property is uncertain which can change. The relevant ministries are expected to immediately issue technical regulations related to intellectual property-based financing so that they can serve as guidelines and provide legal certainty in implementing intellectual property-based financing for creative economy actors.